Purchasing Decision Models Through Customer Satisfaction: Analysis Of Service Quality And Prices In The City Of Padang - Emil Salim (Journal Of Science Education And Management Business, 2023)
This study aims to determine how big the influence of service quality and price on purchasing decisions with customer satisfaction as an intervening variable. The research variables are Service Quality, Price, Purchase Decision, and Customer Satisfaction. The analytical method used is Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS). To test the hypothesis, the Path Coefficient is used, which is a test carried out to see the direct effect and the Indirect Effect is a test that aims to see the indirect effect. The findings from this research show that service quality has an impact on purchasing decisions, while price does not have a significant impact on purchasing decisions. And lastly, it was proven that the intervening variable was able to mediate the independent variable.